Utilization of peltier chipsets in electric vehicles to charge li-ion batteries - AKAR, ONUR (My University, 2023)
Using the Peltier effect for power generation is a relatively new technology that has been gaining attention in recent years. Using Peltier chips for power generation in EVs is an interesting approach that has the potential to provide a renewable and sustainable source of energy. By using the heat generated by the car's components during operation, the Peltier chips can generate electricity, which can be used to charge the battery. This approach has several benefits, including reducing the reliance on fossil fuels, improving the efficiency of the vehicle, and reducing the carbon footprint of the EV. The Peltier effect is a thermoelectric phenomenon that converts temperature differences into electrical energy to generate enough power to recharge an electric vehicle battery, several Peltier chips can be connected in series, and a converter can be used to convert the generated voltage into a sufficient voltage and can charge the battery. In this paper, an in-depth exploration will be conducted to evaluate the overall effectiveness and efficiency of Pelter chips, with a particular focus on simulating the utilization of these chips through the utilization of Proteus software.
Keywords: Generate electricity; EV; Li-Ion Battery; Peltier; Charge Unit